Catches Analysis of Scottish Seine Net Modification of Cod-end in Majene Waters, Makassar Strait. Issue 1 (1st December 2022) - Palo, Mahfud; Najamuddin,; Assir, Andi; Sarlan, Syahrul; Jaya, Indra
Abstract: Research on Scottish Seine Net Modification of cod-end was conducted to analyze the catch. This research was carried out in the western coastal waters of Majene Regency, West Sulawesi, following the fishing operation of one unit of Scottish Seine Net, which had modified its fishing gear. The study results found ten species of fish caught with a total catch of 115.4 kg. The four most caught species were Indian scad 46.5 kg, mackerel tuna 21.5 kg, skipjack tuna 19.2 kg, rainbow runner 17.8 kg, and six other species 10.4 kg. The total catch was 115.4 kg consisting of 1753 individuals, with the composition of the species of catch consisting of Indian scad ( Decapterus russelli ) 56.7%, Bigeye scad ( Selar crumenophthalmus ) 22.6%, skipjack tuna ( Katsuwonus pelamis ) 9.9%, Mackerel tuna ( Euthynnus affinis ) 3.1% and the other six species 7.7%. The four most common catch species are the Indian scad, 7.3-25.8 cm. Bigeye scad, 6.5-20.5 cm. Skipjack tuna, 10.8-25.5 cm. And Mackerel tuna, 14.5-45.1 cm. Indian scad as the catch with the highest composition caught 62.7% were suitable for catching.